MON-687 Diabetic Muscle Infarction (DMI) a Rare Under-Recognised Complication of Diabetes Mellitus (DM): A Series of Three Cases - Dhanasekaran, Maheswaran (J Endocr Soc, 2020)
Background: Diabetic muscle infarction (DMI) also known as diabetic myonecrosis is an acute, rare, microangiopathic complication of long-standing poorly controlled Diabetes Mellitus (DM). DMI presents as severe pain and swelling of the affected muscle group, usually of the lower extremities. It generally occurs in patients with established vasculopathy from uncontrolled diabetes including retinopathy and nephropathy. However, a clear association of DMI to long term mortality has not yet been defined. Proposed pathophysiologic mechanisms for DMI are microvascular endothelial damage complicated by thromboembolic events triggering an inflammatory cascade, leading to local tissue ischemia and eventual infarction. Alterations in the coagulation-fibrinolysis system and vasculitis have also been invoked. About 50% of the cases have DMI recurrence in the setting of uncontrolled DM. Clinical Case: We report 3 cases of DMI diagnosed in patients with long-standing poorly controlled DM with at least two established micro-vascular complications. The lower extremity muscle group was affected, especially the thigh muscles and paraspinal muscle in one case. Biochemical parameters were significant for normal white blood cell counts, elevated erythrocyte sedimentation rate (112, 105, 145 mm/hr respectively; n 0–15 mm/hr) and C-reactive protein (CRP) (54.3, 260, 162 mg/L respectively; n 0–5.0 mg/L) and elevated creatine kinase in two cases (539 and 379 U/L; n 5–150 U/L). Infectious work-up including blood cultures were negative. Lower extremity doppler was negative in all three cases. Diagnosis was established with the help of MRI in two cases showing diffuse hyperintensities of the muscle groups involved and muscle biopsy in the third showing neutrophilic and eosinophilic inflammation and areas of necrosis, fibrosis and hemorrhage. Treatment involved adequate pain management and anti-platelet therapy along with tight glycemic control. No recurrence thus far was noticed in all three patients. Conclusion: DMI should be considered in the differential diagnosis of patients with the aforementioned risk factors who did not show a response to antibiotics, as administered for presumed cellulitis. Though self-limiting, studies have shown a long term temporal correlation with increased all-cause mortality in patients with DMI. Hence DMI is considered as another cardiovascular risk equivalent. Further studies are needed to explore strategies aimed at preventing DMI and its recurrence.